The University of South Africa (Unisa) 1918–1948: the first transition, from colonial to segregationist institution. (2nd January 2016) - Manson, Andrew
ABSTRACT: This article traces the first of what would become several significant transitions in the evolution of the University of South Africa (Unisa); that from University of the Cape of Good Hope (UCGH), an institution with a distinct English tradition loosely based on the 'liberal' constitution of the Cape Colony, to a more segregationist Afrikaner-dominated university by 1946. This was largely shaped by national politics, in particular the rise of Afrikaner nationalism, in the 1920s and 30s. Not only did Unisa become captive to Afrikaner forces, it also was strongly infiltrated by the Broederbond, which had as one of its objectives the holding of key positions in higher education in South Africa. In addition, issues of race now became a growing 'problem' as Unisa sought to fulfil its mandate to provide higher education for 'non-Europeans' in an era of segregation. However, it would be a distortion to portray this transition fom a simple binary perspective. There was ambivalence about the 'liberalism' of the UCGH that reflected the pressures for a new racial order at the Cape. Similarly, the extent of Broederbond influence at Unisa (and over national politics) should not be over-emphasised. Somewhat paradoxically, Unisa continued to accommodate nodes of liberal thinking within the institution, and in the 1960s resisted state attempts to be drawn into a scheme to construct an Afrikaans-only university in Johannesburg. Nevertheless, the essential conservatism and political acquiescence of the university to apartheid meant that the requirement to transform Unisa in the democratic era was all the more painful and complex.